Prevention and management of ovarian hyperstimulation syndrome. Issue 151 (March 2017) - Nelson, Scott M.
ABSTRACT: Ovarian hyperstimulation syndrome (OHSS) is a serious iatrogenic complication of ovarian stimulation. It is feasible to identify patients at risk, modify stimulation strategies to ameliorate risk, and initiate out-patient treatments that alter disease pathophysiology to reduce disease severity. Mitigation of OHSS risk and severity, through innovative approaches prior to treatment, during treatment and after treatment should now be standard care. This review summarizes recent developments and provides recommendations on the prevention and treatment of OHSS.